Reading Humboldt through the theory of communicative action - McLuskie, Ed (Javnost (Ljubljana), 2003)
Wilhelm von Humboldt's studies of language during the nineteenth century anticipated twentieth-century symbolic interactionism, suggesting a two-century intellectual history stressing the communicating subject as an intersubjective actor. Jürgen Habermas's theory of communicative action, well known for its inclusion of George Herbert Mead's symbolic interactionism, appeals in the same breath to von Humboldt's work, thus inviting a critical re-appropriation of Mead beyond the social-psychological realm, into macro-level analyses of cultural reproduction and societal evolution. Read as a project of cultural cultivation, the model of the conversation achieves the status of life-giver for language as such. This project reaches the level of state interests to maintain individual creativity in the company of others, toconsider language an explicit project of social and cultural policy, and to develop concrete institutions of education in the interest of the emancipated citizen. However, this rearticulated symbolic interactionism faces theory-practice disparities in a weak legacy of educational diversity.
Keywords: Humboldt, Wilhelm von, 1767-1835; communication; komuniciranje; sporazumevanje; razgovor; Language; jezik; medosebne komunikacije; interakcije; social psychology; socialna psihologija